Identifying suitable locations for solar energy production as a source of clean energy in Dukan district - سعید, ا.م.د. باكيزا عزيز سعيد; رشید, شیراز عوسمان رشید (Sulaimani Journal for Humanities, 2025)
With the escalation of global environmental crises and rising energy demand, the shift towards renewable sources has become a strategic imperative. Solar energy, as a limitless and clean resource, represents a critical alternative for reducing dependency on fossil fuels and limiting greenhouse gas emissions. The primary objective of this study is to assess site suitability for the establishment of solar farms in the Dukan District, utilizing Geographic Information System (GIS) technology to identify the most appropriate locations, The research employs a descriptive-analytical methodology, relying primarily on spatial analysis. This is accomplished by constructing a site suitability model that analyzes several layers of geographic data, including solar radiation, a Digital Elevation Model (DEM) to determine land slope and aspect, land use maps, and proximity to economic infrastructure such as electricity grids and roads. Ultimately, the study demonstrates how solar energy development can reduce dependence on private generators, decrease harmful gas emissions, and achieve sustainable development in the region. The potential energy production from solar power in the Dokan District is estimated to be 4318.68 Gigawatt-hours (GWh), equating to an annual reduction of between 1597912 and 3023076 tons of carbon dioxide, depending on the type of fuel it replaces.
Keywords: Renewable Energy; Solar Energy; CO2eq; Greenhouse Gases (GHG); Geographic Information System (GIS)